LncRNA GAS5 downregulates NLRP3 inflammasome activation-mediated pyroptosis in sepsis-induced myocardial injury by targeting SIRT3/AMPKα - Luo, Minghao; Peng, Yuce; Lv, Dingyi; Xue, Yuzhou; Huang, Longxiang; Hu, Yu; Zhu, Wenyan; Luo, Suxin; Shen, Jian; Li, Xiang (Heliyon, 2023)
An increasing body of studies has demonstrated the significance of long non-coding RNA (lncRNA) growth arrest specific 5 (GAS5) in inflammation and myocardial injury in septic shock. This research aims to determine whether GAS5 contributes to the pathological development of sepsis-induced cardiac damage and NLRP3 inflammasome-mediated myocardial cell pyroptosis. Cecal ligation and puncture (CLP) surgery was used to cause septic shock in C57BL/6 wild-type mice. After CLP, inflammatory, pyroptosis parameters of myocardial tissue, survival rate, and Murine Sepsis Score (MSS) were assessed to evaluate the involvement of GAS5 in the mouse myocardial depression. To investigate GAS5's function in lipopolysaccharide (LPS) induced myocardial cell pyroptosis, gain- and loss-of-function experiments were conducted in vitro on HL-1 cells. Our findings indicated that CLP dramatically reduced survival rates, MSS, SIRT3 and p-AMPK expression, and activated the Nuclear factor-κB (NF-κB) pathway and NLRP3 inflammasome-mediated pyroptosis. The NF-κB and pyroptosis pathways were greatly elevated while SIRT3/p-AMPKα was dramatically decreased as a result of GAS5 being downregulated. Meanwhile, the regulatory effect could be suppressed by SIRT3 and AMPKα activator. Our observations supported the idea that GAS5 has a crucial protective impact against myocardial inflammation and pyroptosis in sepsis.